Resilience conceptual framework for assessing the performance of transit service. Issue 3 (2nd July 2020) - Chang, Justin S.; Jung, Dongjae; Jun, Seohee; Oh, Hyerim
ABSTRACT: Traditionally, the performance of transit service has been assessed using the framework of level of service or quality of service. This study proposes a novel platform for evaluating performance in the context of resilience. The term resilience represents the ability of a system to absorb and recover from shocks. The concept is thus useful to monitor the degradation and recovery of transit service. This new model is applied to Seoul Metro Line 7 using frequency as the service attribute that could degrade due to a system shock. An empirical study analysing train operations data assesses the dynamic and disaggregate nature of performance of transit service. This feature is understood to add useful insights to the existing evaluation frameworks because the proposed approach can represent the real and perceived performance of transit service. The performance using this framework is impacted by distance from the terminal stations and time-of-day characteristics. Three issues including the level of demand, the form of indicator, and the time unit of analysis are also discussed. Finally, recommendations for further studies, particularly around the theme of factors affecting the performance of transit service and a comparative analysis between the proposed framework and the conventional approaches involving level of service and quality of service, are presented.